Selective frequency mixing in a cascaded self-Raman laser with a critical phase-matched LBO crystal - Duan, Yanmin (2023)
Selective frequency mixing in a cascaded Nd:YVO4 self-Raman laser was investigated for wavelength-switchable visible light output. Phase-matching with temperature tuning of both critical and non-critical phase-matched LBO crystals was analyzed. The critical phase-matched LBO crystal with θ = 86.0° and φ = 0° generated five discrete visible wavelengths by frequency mixing among the fundamental, first, and second Stokes waves, without sub-zero °C cooling. While laser performance examination was experimentally limited to frequency conversion of the first and second Stokes fields, average output power across three visible wavelengths was high, at 2.2, 1.31, and 1.58 W for 588, 620, and 657 nm, respectively, for the incident power of 15.5 W. This is promising for practical laser sources with multi-wavelength tunability across the visible spectrum. Such lasers can replace numerous single-line sources for various applications.